ANTI-MOTIVATION IN THE EDUCATIONAL ACTIVITIES OF ELEMENTARY SCHOOL STUDENTS FROM THE PERSPECTIVE OF STUDENTS AND TEACHERS - Ivanova, Natalia; Minaeva, Elena; Suvorova, Olga; Kolesova, Oksana; Mamonova, Elena; Akpaeva, Asel (Revista Inclusiones, 2020)
The article presents the results of empirical research aimed at studying the characteristics of antimotivation in the educational activities of children of elementary school age. As the main method for obtaining and interpreting empirical data, the authors used the content analysis of essays on the topic "Why don’t some children like to study?". The choice of this method was conditioned by the lack of valid and reliable methods for studying anti-motivation in the educational activities of Russian elementary school students. The authors compared anti-motivation in educational activities from the point of view of elementary school teachers and students as the main subjects of education. According to the results of the study, it was found that, from the position of teachers, a greater number of anti-motivational factors were associated with the content of educational activities and students had a more pronounced personal attribution of anti-motivation in education. Both respondent groups believed that grade-related factors did not play a significant role in providing anti-motivation for the educational activities of elementary school students. Organizational and interpersonal antimotivational factors had similar average indicators in both groups of respondents. The study made it possible to highlight a set of educational activity anti-motives for their further inclusion in a special questionnaire on the study of anti-motivation of the educational activities of elementary school students.